E-Archive Development In PT Haleyora Powerindo Sorong - Annisa Nurul Sucianingsih Palisoa; Melda Agnes Manuhutu (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
The development of e-archives is a part of an effort to completely manage to archive at PT Haleyora Powerindo Sorong. This research aims to see the factors that cause e-archives cannot be used optimally and also to develop e-archives as needed. The analytical method is a prototype method. The result of this research is the creation of electronic archives that have been developed with innovative and solutive design, menus and function that answer the factors that cause e-archive not be used optimally.